The complete plastid genome of Cheniella didyma (H.Y.Chen) R.Clark & Mackinder (Leguminosae). Issue 1 (2nd January 2022) - Zeng, Qiubiao; Gu, Shiran; Ma, Zhonghui; Tu, Tieyao
Abstract: We report here for the first time the complete plastid genome of Cheniella didyma of the legume family. The plastid genome has a typical circular structure with a total length of 157, 186 bp and contains two inverted repeat regions (IRs, 24, 455 bp), a large single-copy region (LSC, 89, 410 bp), and a small single-copy region (SSC, 18, 866 bp). This is the first report of the complete plastid genome sequence of Cheniella, a genus recently segregated from Bauhinia s.l. The phylogenetic analysis based on 77 coding regions of the plastome of this species and those of the related species strongly suggested that C. didyma is sister to Lysiphyllum and is not directly related to Bauhinia s.s.